PENGARUH KOMPETENSI DAN KINERJA GURU TERHADAP HASIL BELAJAR SISWA DI MADRASAH TSANAWIYAH MIFTAHUL ULUM DENPASAR BALI TAHUN AJARAN 2024/205 - HOTIJAH; Ni Luh Putu Yesy Anggreni; Luh De Liska (Program Studi Pendidikan Ekonomi Universitas PGRI Mahadewa Indonesia, 2025)
This study aims to determine the effect of teacher competence on student learning outcomes at Madrasah Tsanawiyah Miftahul Ulum Denpasar Bali in the 2024/2025 Academic Year. The effect of teacher performance on student learning outcomes at Madrasah Tsanawiyah Miftahul Ulum Denpasar Bali in the 2024/2025 Academic Year. The effect of teacher competence and performance together on student learning outcomes at Madrasah Tsanawiyah Miftahul Ulum Denpasar Bali in the 2024/2025 Academic Year. This study uses a quantitative approach with data collection techniques of observation, interviews, documentation and questionnaires which took 100 respondents/students. The results of this study indicate that (1) There is a significant effect of competence on student learning outcomes at MTs. Miftahul Ulum Denpasar. This is proven by the t-value of 3.818 which means it is greater than the t-table of 1.984 (3.818 > 1.984) meaning H0 is rejected and Ha is accepted, which means teacher competence (X1) has a significant partial influence on student learning outcomes (Y) at MTs. Miftahul Ulum Denpasar. (2) There is a significant influence of teacher performance on student learning outcomes at MTs. Miftahul Ulum Denpasar. This is proven by the t-value of 16.250 which means it is greater than the t-table of 1.984 (16.250 > 1.984) which is in the H0 rejection area, meaning H0 is rejected and Ha is accepted, which means teacher performance (X2) has a significant partial influence on student learning outcomes (Y) at MTs. Miftahul Ulum Denpasar. (3) There is a significant influence of teacher competence and performance together on student learning outcomes at MTs. Miftahul Ulum Denpasar. This is proven by the value obtained by the F count value of 95.210 > from F table, 95.210 > 3.09 so that H0 is rejected and Ha is accepted. The results of the determination coefficient show that the Adjusted R Square is 0.766, which means that 76.6% of the variation in learning outcomes (Y) is influenced by teacher competence (X1) and teacher performance (X2) while the remaining 24.4% is influenced by other factors that are not included in the research model.